Fusion and failure following anterior cervical plating with dynamic or rigid plates: 6-months results of a multi-centric, prospective, randomized, controlled study - Stulik, Jan; Pitzen, Tobias Rainer; Chrobok, Jan; Ruffing, Sabine; Drumm, Jörg; Sova, Laurentius; Kucera, Ravel; Vyskocil, Tomas; Steudel, Wolf Ingo (European spine journal, 2007)
Anterior cervical plate fixation is an approved surgical technique for cervical spine stabilization in the presence of anterior cervical instability. Rigid plate design with screws rigidly locked to the plate is widely used and is thought to provide a better fixation for the treated spinal segment than a dynamic design in which the screws may slide when the graft is settling. Recent biomechanical studies showed that dynamic anterior plates provide a better graft loading possibly leading to accelerated spinal fusion with a lower incidence of implant complications. This, however, was investigated in vitro and does not necessarily mean to be the case in vivo, as well. Thus, the two major aspects of this study were to compare the speed of bone fusion and the rate of implant complications using either rigid- or dynamic plates. The study design is prospective, randomized, controlled, and multi-centric, having been approved by respective ethic committees of all participating sites. One hundred and thirty-two patients were included in this study and randomly assigned to one of the two groups, both undergoing routine level-1- or level-2 anterior cervical discectomy with autograft fusion receiving either a dynamic plate with screws being locked in ap - position (ABC, Aesculap, Germany), or a rigid plate (CSLP, Synthes, Switzerland). Segmental mobility and implant complications were compared after 3- and 6 months, respectively. All measurements were performed by an independent radiologist. Mobility results after 6 months were available for 77 patients (43 ABC/34 CSLP). Mean segmental mobility for the ABC group was 1.7 mm at the time of discharge, 1.4 mm after 3 months, and 0.8 mm after 6 months. For the CSLP- group the measurements were 1.0, 1.8, and 1.7 mm, respectively. The differences of mean segmental mobility were statistically significant between both groups after 6 months (P = 0.02). Four patients of the CSLP-group demonstrated surgical hardware complications, whereas no implant complications were observed within the ABC-group (P = 0.0375). Dynamic plate designs provided a faster fusion of the cervical spine compared with rigid plate designs after prior spinal surgery. Moreover, the rate of implant complications was lower within the group of patients receiving a dynamic plate. These interim results refer to a follow-up period of 6 months after prior spinal surgery. Further investigations will be performed 2 years postoperatively.
Keywords: Radiography; Middle Aged; mužské pohlaví; studie případů a kontrol; Prospective Studies; neúspěšná terapie; kostní destičky; ženské pohlaví; Treatment Failure; radiografie; Humans; prospektivní studie; fúze páteře; Spinal Fusion; lidé středního věku; Bone Plates; krční obratle; Case-Control Studies; Female; Cervical Vertebrae; lidé; Male